Lymph Node Cytopathology - Pambuccian, Stefan E.; Bardales, Ricardo H.; SpringerLink (Online service) (Boston, MA : Springer US : Imprint: Springer, 2011)
Lymph Node Cytopathology by Stefan E. Pambuccian, MD, and Ricardo H. Bardales, MD, will fulfill the need for an easy-to-use and authoritative synopsis of lymph node cytopathology. This volume, part of the Essentials in Cytopathology book series, fits into the lab coat pocket and is ideal for portability and quick reference. Each volume in the series is heavily illustrated with a full color art program, while the text follows a user-friendly outline format. Stefan E. Pambuccian, MD, is Director of Cytopathology and Cytopathology Fellowship Program in the Department of Laboratory Medicine and Pathology and Department of Otolaryngology at the University of Minnesota, Minneapolis, Minnesota. Ricardo H. Bardales, MD, is Pathologist at Outpatient Pathology Associates, Sacramento, California.
Introduction -- Overview of Ancillary Methods in Lymph Node FNA diagnosis -- Lymphadenopathy: Anatomic and Clinical Clues to Fine Needle Aspiration Diagnosis -- Cytology of Normal/Reactive Lymph Nodes -- Overall assessment of the aspirate: Diagnostic clues -- Overview of the algorithmic pattern-based approach to lymph node FNA -- The Polymorphous Lymphoid Cell Pattern -- The Monotonous Small-Cell Pattern -- The Monotonous Intermediate-Size Cell Pattern -- The Monotonous Large Cell Pattern -- The Pleomorphic Cell Pattern -- Infectious and Non-Infectious Lymphadenitis -- Unusual Neoplastic and Nonneoplastic Conditions of Lymph Nodes -- Pitfalls and Limitations of FNA of Lymph Nodes -- Index.
Keywords: Medicine; Oncology; Pathology; Medicine & Public Health; Pathology; Oncology